A Simple Model of Mergers and Innovation - Giulio Federico; Gregor Langus; Tommaso M. Valletti (Center for Economic Studies and ifo Institute (CESifo), 2017)
We analyze the impact of a merger on firms' incentives to innovate. We show that the merging parties always decrease their innovation efforts post-merger while the outsiders to the merger respond by increasing their effort. A merger tends to reduce overall innovation. Consumers are always worse off after a merger. Our model calls into question the applicability of the “inverted-U” relationship between innovation and competition to a merger setting.
Keywords: D43; G34; L40; O30; 330; innovation; R&D; mergers